1997
DOI: 10.1046/j.1469-8137.1997.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of propagules of arbuscular mycorrhizal fungi in soils in eastern Australia used to grow cotton

Abstract: SUMMARYSoil-borne spores and hj^phae of arbuscular mycorrhizal fungi are important propagules in cracking clay soils of northern NSW, Australia. In these soils, senescent roots were uncommon. Although c. 4-200 spores g~^ soil were found, less than 6 % established arbuscular mycorrhizas in trap plants, and this percentage declined over 24 months. Using tetrazolium red as a vital stain, 16-21 % of spores from field soils were found to be viable in fresh soil and 6-7 % after 24 months of storage. Using fluorescei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 32 publications
1
22
0
3
Order By: Relevance
“…Alternatively, colonization at depth might have arisen from hyphae or spores in soil or senescent roots. Hyphae growing from colonized senescent roots can establish mycorrhizas (Tommerup & Abbott, 1981), although McGee et al (1997) concluded that senescent roots made a negligible contribution to the colonization of plants and our results support that conclusion. It is unlikely that fresh roots intercepted senescent roots colonized by AM fungi by following previous lines of root growth.…”
Section: supporting
confidence: 82%
“…Alternatively, colonization at depth might have arisen from hyphae or spores in soil or senescent roots. Hyphae growing from colonized senescent roots can establish mycorrhizas (Tommerup & Abbott, 1981), although McGee et al (1997) concluded that senescent roots made a negligible contribution to the colonization of plants and our results support that conclusion. It is unlikely that fresh roots intercepted senescent roots colonized by AM fungi by following previous lines of root growth.…”
Section: supporting
confidence: 82%
“…McGee, et al (1997), utilizando o mesmo método, encontraram 20 % de esporos viáveis em amostras de solo recém-coletadas, que diminuíram para 6-7 % após dois anos de estocagem. No presente estudo, o período de estocagem foi ao redor de um ano.…”
Section: Resultados E Discussão Esporos Viáveis E Não-viáveisunclassified
“…The small volume of soil should not affect the initiation of infection, or the initial spread of infection within the roots. It is likely that the small volume of soil affected the shoot growth of the seedlings, and the data obtained do not indicate the mycorrhizal effect on plant growth which we have demonstrated elsewhere (Pattinson et al, 1997).…”
Section: Discussionmentioning
confidence: 64%
“…It IS likely that the soils contained more propagules tban were necessary to initiate maximum rates of infection as suggested by McGee et al (1997). Tbe result of excess propagules would be to mask effects of factors tbat deplete the number of propagules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation